COMPARATIVE STUDY OF DIFFERENT COOKING TO THE NUTRIENT CONTENT OF FISH FLOUR FROM MUDSKIPPER (Periophthalmusminutus) - tari, Yurina; Edison, Edison; Sukmiwati, Mery (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACTThis study aimed to determine the nutrient content of mudskipper fish flour with different cooking. The method used in this research was a comparative experiment method,with the T-test consistedof two treatments. There were steaming (P1) and boiling (P2) with three replications, obtained 6 experimental units. The parameters measured in this research were the yield and the analysis of nutrient content (protein content, moisture content, ash content, and fat content). Based on the results of research obtained the best treatment was steaming with a yield rate of 16.56%, the of protein content 77.96%, moisture content of 5.23%, fat content of1.48% and ash content of 13.67%. The cooking treatment had a significant effect on the protein content and the moisture content of the fish flour from mudskipper (Periopthalmusminutus) produced.Keywords: boiling, fish flour, mudskipper, and steaming